A case of W. chitiniclastica bacteremia in a 38-year-old homeless male originating from a maggot-infested amputated foot - Ashlyn Lipnicky; Praveen Subramanian; Wissam El Atrouni (IDCases)
Wohlfahrtiimonas (W.) chitiniclastica was first isolated from the larval stage of the fly vector Wohlfahrtia magnifica. It is a gram-negative, non-motile, strictly aerobic rod that thrives in temperatures between 28º C and 37º C. Its strong chitinase activity aids in metamorphosis, which suggests a symbiotic relationship with the fly. Although rare, W. chitiniclastica has been implicated in human infections, like bacteremia and osteomyelitis, typically transmitted through fly larvae in skin wounds. Over the past decade, there have been 12 documented human infections, including five confirmed cases of bacteremia. We present a case involving a 38-year-old homeless male with W. chitiniclastica bacteremia secondary to maggot-infested wounds. The patient had a medical history of late latent syphilis and previous frostbite requiring right transmetatarsal amputation and presented with a stump infection on the right foot, featuring maggots. He was afebrile with stable signs and blood cultures revealed W. chitiniclastica. The pathogen was susceptible to various antibiotics, including cefepime, piperacillin/tazobactam, meropenem, trimethoprim-sulfamethoxazole, and levofloxacin. The patient was treated with piperacillin/tazobactam and later transitioned to oral trimethoprim-sulfamethoxazole but left against medical advice. This case underscores the intersection of infectious diseases and social inequalities, highlighting the need for clinicians to consider W. chitiniclastica in patients with poor hygiene, alcoholism, peripheral vascular disease, and open wounds. It also emphasizes the dual role of maggots in wound care, capable of both cleaning necrotic tissue and introducing pathogenic bacteria.